Modeling of crude distillation unit (CDU) - Muhammad Safwan, Taharim (2012)
Crude distillation unit (CDU) is a complex process in the field of separation which produces wide range of products at different stages under different conditions.The products of the process were heavy naphtha,kerosene,diesel,atmospheric gas oil and reduced crude.However,the dynamic and multivariable nature with strict quality was makes it difficult to operate the process units steadily.More,the dynamics of CDU are complex due to its complex vapor-liquid equilibrium relationships.It is necessary to predict the new steady-state values for any changes in the operating conditions.This research aims to develop a steady-state model for CDU based on the fundamental modeling approach. The simulation was carried out in Aspen Plus.The effect of feed flow rate,feed composition and steam flow rate on product compositions and tray temperatures were studied.The results were compared with the data available in the literature and the accuracy of the model has been proved.